Terlipressin-Induced Skin Necrosis in 3 Cases: Should We Concern? - Küçükdemirci, Ömer; Bektaş, Ahmet (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Küçükdemirci Ö, Bektaş A. Terlipressin-induced skin necrosis of 3 cases: should we concern? Turk J Gastroenterol. 2025;36(3):193-196.